2013
DOI: 10.1021/am4017945
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitroso-N-acetylpenicillamine (SNAP) Derivatization of Peptide Primary Amines to Create Inducible Nitric Oxide Donor Biomaterials

Abstract: An S-nitroso-N-acetylpenicillamine (SNAP) derivatization approach was used to modify existing free primary amines found in fibrin (a natural protein-based biomaterial) to generate a controlled nitric oxide (NO) releasing scaffold material. The duration of the derivatization reaction affects the NO release kinetics, the induction of controlled NO-release, hydrophobicity, swelling behavior, elastic moduli, rheometric character, and degradation behavior. These properties were quantified to determine changes in fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…The SNAP approach provides a robust procedure to functionalize both natural and synthetic peptides bearing amine residues (e.g., lysine) to form NO donors. For instance, a natural protein, fibrin, was decorated with SNAP with the formation of NO-releasing peptide and the resulting peptide can remarkably inhibit bacterial adhesion compared with natural fibrin without NO-releasing capability (Vanwagner et al, 2013). Besides peptides, natural polysaccharides and oligosaccharides could also be modified with the formation of SNO-type NO donors.…”
Section: S-nitrosothiol (Sno)-based No Polymeric No Donorsmentioning
confidence: 99%
“…The SNAP approach provides a robust procedure to functionalize both natural and synthetic peptides bearing amine residues (e.g., lysine) to form NO donors. For instance, a natural protein, fibrin, was decorated with SNAP with the formation of NO-releasing peptide and the resulting peptide can remarkably inhibit bacterial adhesion compared with natural fibrin without NO-releasing capability (Vanwagner et al, 2013). Besides peptides, natural polysaccharides and oligosaccharides could also be modified with the formation of SNO-type NO donors.…”
Section: S-nitrosothiol (Sno)-based No Polymeric No Donorsmentioning
confidence: 99%
“…Genipin-cross-linked fibrin exhibited promise in functioning as an adhesive for repairing intervertebral disc annulus while demonstrating elastic modulus in the range of native annular tissue and remained adhered to the native tissue at strains exceeding physiological levels. Most recently, fibrin gel was functionalized with nitric oxide donors for preparing biomaterials capable of controlling release of nitric oxide for promoting tissue regeneration and wound healing [ 61 , 62 ].…”
Section: Future Outlookmentioning
confidence: 99%
“…The well-known NO donor, S-nitroso-N-acetyl penicillamine (SNAP), has been used to release NO through photolytic cleavage of the S-N bond 25 . For use in clinical applications, recent studies have demonstrated the potential for NO release through compressive and shear mechanisms in addition to thermal mediated pathways, presenting a more clinically relevant and viable option for the application of site specific controlled NO release 1 .…”
Section: Introductionmentioning
confidence: 99%